The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/mib.0000000000001220
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Drug Levels and Endoscopic Recurrence in Postoperative Patients with Crohnʼs Disease Treated with Tumor Necrosis Factor Inhibitors

Abstract: Seventy-three consecutive patients (32-infliximab, 41-adalimumab) were included in the study. The colonoscopies were performed after a median of 15 (7-43) months after surgery and 8 (6-15) months from treatment onset. SER was demonstrated in 26/73 (35.6%) of the patients. The need for dose optimization, as well as trough infliximab levels (2.4 μg/mL [0.45-4.1] versus 1.1 (0-0.6), P = 0.008) and presence of antidrug antibodies (1/18 [5.6%] versus 10/14 [71.4%], P = 0.0001) were significantly associated with a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…The clinical trial assessed the effectiveness of IFX in preventing postoperative recurrence in 297 patients who were randomized into a group that received IFX 5 mg/kg and another that received placebo every 8 weeks for 200 weeks, with the primary outcome being assessed for clinical recurrence and the secondary, endoscopic recurrence. (17) The retrospective cohort in adults included 73 consecutive postoperative patients treated with IFX (32 patients) or adalimumab (41 patients) (18) . For this qualitative analysis, only data from patients using IFX were used.…”
Section: Included Eligibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical trial assessed the effectiveness of IFX in preventing postoperative recurrence in 297 patients who were randomized into a group that received IFX 5 mg/kg and another that received placebo every 8 weeks for 200 weeks, with the primary outcome being assessed for clinical recurrence and the secondary, endoscopic recurrence. (17) The retrospective cohort in adults included 73 consecutive postoperative patients treated with IFX (32 patients) or adalimumab (41 patients) (18) . For this qualitative analysis, only data from patients using IFX were used.…”
Section: Included Eligibilitymentioning
confidence: 99%
“…TABLE 2 shows in detail the characteristics of the included studies, as well as the clinical and demographic aspects of the patients. Characteristics of the studies Of the four articles included for the qualitative analysis, one was a prospective cohort study (16) , one was a randomized clinical trial (17) and two were retrospective cohort studies (18,19) , the last being exclusively in pediatric patients (19) . The number of patients ranged from 11 to 297, totalizing 404 patients included in the selected studies (16,17) .…”
Section: Included Eligibilitymentioning
confidence: 99%
“…Moreover, we did not have data on immunogenicity that might be particularly relevant in the case of reinitiation of infliximab, which might have favored adalimumab. However, recent studies showed controversial results regarding the utility of trough drug levels to predict the efficacy of anti-TNF in preventing endoscopic POR ( 28 30 ). Second, endoscopic images were not recorded, and no central reading was possible; therefore, the information regarding the Rutgeerts endoscopic score relied on local endoscopic reports.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies employed similar outcome measures (e.g. post-operative recurrence [31,39,55] or mucosal healing after 1 year [29,45,66]) and were thus suitable for meta-analysis. However, the studies in both the primary and the secondary outcomes did not report exact summary measures or the frequencies in which the outcomes of interest occurred in male and female patients.…”
Section: Meta-analysismentioning
confidence: 99%
“…Of the included studies involving multiple biologicals, seven examined a population treated with adalimumab or infliximab [15,25,31,39,46,48,51,55,64] and one concerned IBD patients treated with adalimumab, certolizumab or infliximab [36]. The first group of studies were all of a retrospective nature, with varying populations of CD patients, UC patients or both, as described in Table 2.…”
Section: Studies Examining Multiple Biologicalsmentioning
confidence: 99%